Antagonistic effects of trifluoperazine, imipramine, and chlorpromazine against acetylcholine-induced contractions in isolated rat uterus - Balais Samira Youssel Hussein; Prado Wilian Alves; Alves-Do-Prado Wilson (Acta Pharmacologica Sinica, 2016)
AIM: To examine the effects and affinity of some phenothizines (trifluoperazine, Tri and chlorpromazine, Chl) and antidepressant (imipramine, Imi) drugs on acetylcholine (ACh)-induced uterine contraction. METHODS: Isotonic contractions of rat uterine strips were recorded. ACh was administrated to induce maximal contraction before exchange of nutrient solution. ACh was added 5 min after the testing drugs. The nutrient solution was exchanged 4 times after each agonist (ACh or other agents) to produce maximal contraction. RESULTS: Atropine (Atr, 0.029-2.9 mumol.L-1), 4-DAMP (3.6-360 nmol.L-1), pirenzepine (Pir, 0.23-23.5 mumol.L-1), and AF-DX 116 (0.7-35.6 mumol.L-1) competitively antagonized the muscular uterine concentration induced by ACh (0.068-36068 mumol.L-1). The Schild plot was linear (r = 1.00). The pKB and slopes values (95% confidence limits) were 9.28 +/- 0.12 and 1.00 +/- 0.10 to Atr, 9.06 +/- 0.10 and 1.10 +/- 0.08 to 4-DAMP, 7.03 +/- 0.15 and 0.99 +/- 0.12 to Pir, and 5.60 +/- 0.08 and 1.00 +/- 0.19 to AF-DX 116. Tri 0.01-2 mumol.L-1 (pKB = 8.39 +/- 0.04) and Imi 94-940 nmol.L-1 (pKB = 7.21 +/- 0.10) produced also a competitive antagonism of the muscular uterine contraction induced by ACh (r = 1.00), but the slope was only 0.60 +/- 0.03 to Tri or 0.83 +/- 0.16 to Imi. Chl 2.8-5.6 mumol.L-1 produced a weak antagonism on amplitude of muscular contraction induced by the cholinomimetic. CONCLUSION: The muscarinic receptors on uterus behaved as M3 subtype. Tri and Imi, but not Chl, were competitive antagonist of muscarinic receptors of uterus. Imi behaved a simple competitive antagonist at a single site on myometrium, but Tri was not a simple competitive agent at a single site.